2019
DOI: 10.22487/j24077593.2019.v6.i1.12697
|View full text |Cite
|
Sign up to set email alerts
|

Host Range Pantoea Ananatis the Causal Agent of Bacterial Leaf Blight on Allium Spp.

Abstract: Bacterial leaf blight disease caused by Pantoea ananatis has been reported affects some species of Allium spp. Here, we determined the species of Allium spp. that are not the hosts of the P.ananatis through a host range test. The study designed as a completely randomized design with five replications. Pathogenic bacteria of P. ananatis inoculated to shallot, onion, spring onion, garlic, chives, leek, and cung spring onion in the greenhouse of the Faculty of Agriculture Tadulako University. The incubation perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…From the previous studies, there were moulds found in cocoa beans during and post harvesting process. They were from genus Aspergillus, Penicillium, Fusarium, Rhizopus, and Mucor [20,21,22]. Moulds that grow on fruits could be reduced by irradiation treatment with irradiation dose of 1.5 to 3.5 kGy [23].…”
Section: Gamma Irradiators For Plant Industriesmentioning
confidence: 99%
“…From the previous studies, there were moulds found in cocoa beans during and post harvesting process. They were from genus Aspergillus, Penicillium, Fusarium, Rhizopus, and Mucor [20,21,22]. Moulds that grow on fruits could be reduced by irradiation treatment with irradiation dose of 1.5 to 3.5 kGy [23].…”
Section: Gamma Irradiators For Plant Industriesmentioning
confidence: 99%